2021
DOI: 10.3390/jfb12020028
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of a New Mucoadhesive Oral Formulation Based on Sodium Chondroitin Sulfate, Xyloglucan and Glycerol

Abstract: Background: The study aimed at assessing the mucoadhesive properties and the barrier effect of a formulation, labelled as AL2106, containing sodium chondroitin sulfate (ChS), xyloglucan from tamarind seed extract, and glycerol, by evaluating the capacity to adhere to a layer of mucin, the rheological synergism and the barrier effect in comparison to the marketed Esoxx One medical device. AL2106 is a medical device distributed by Alfasigma SpA, Italy with REF FTP57 (Manufacturer: Labomar SpA); it is analogous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Such a rheological synergy implies an intimate interaction with mucin proposing formulation capability of mucoadhesion to ocular tissues. 39 The present results demonstrated that although a positive rheological synergism occurred for all tested formulations, the highest Δη % was observed with Fas/PL-Lipo P407/HPMC gel (Figure 5B). The enhanced mucoadhesion observed for Fas/PL-Lipo P407/HPMC gel compared to Fas/PL-Lipo P407 gel indicates synergistic effect of the combination of P407 and HPMC on extending precorneal residence time which may be contributed to the weak chemical bonds formed between wetted and swelled mucoadhesive HPMC chains and mucin particles introducing prolonged adhesion of the hydrogel at the mucosal surface.…”
Section: In Vitro Mucoadhesion Studymentioning
confidence: 53%
“…Such a rheological synergy implies an intimate interaction with mucin proposing formulation capability of mucoadhesion to ocular tissues. 39 The present results demonstrated that although a positive rheological synergism occurred for all tested formulations, the highest Δη % was observed with Fas/PL-Lipo P407/HPMC gel (Figure 5B). The enhanced mucoadhesion observed for Fas/PL-Lipo P407/HPMC gel compared to Fas/PL-Lipo P407 gel indicates synergistic effect of the combination of P407 and HPMC on extending precorneal residence time which may be contributed to the weak chemical bonds formed between wetted and swelled mucoadhesive HPMC chains and mucin particles introducing prolonged adhesion of the hydrogel at the mucosal surface.…”
Section: In Vitro Mucoadhesion Studymentioning
confidence: 53%
“…To uphold the uniqueness of our research on efficacy assessment, it has been crucial to compare our findings with studies involving HA by itself and in combination with other compounds. Numerous investigations have illustrated the favorable impact of HA and chondroitin sulfate on mucosal protection [25]. Nonetheless, TAMIXAM ® distinguishes itself through its exclusive composition, encompassing both HA and TSX.…”
Section: Discussionmentioning
confidence: 99%
“…Rheology is thus used as an experimental tool for the evaluation of mucoadhesivity in new formulations. In one recent example [74], the mucoadhesive properties of a formulation containing sodium chondroitin sulfate, XG and glycerol were evaluated in vitro by determining the rheological synergy of the mixture, as well as other techniques, such as the direct measurement of adhesion forces.…”
Section: Mucoadhesivity Of Xgmentioning
confidence: 99%